A case report: Pavlovian conditioning as a risk factor of heroin 'overdose' death - Bácskai Erika; Gerevich József; Farkas Lajos; Danics Zoltán (BMC, 2005)
Abstract Background The authors present a case illustrating a mechanism leading directly to death which is not rare but has received little attention. Case presentation The case was evaluated by autopsy, investigation of morphine concentration in the blood, and clinical data. The heroin dose causing the 'overdose' death of a young man who had previously been treated a number of times for heroin addiction did not differ from his dose of the previous day taken in the accustomed circumstances. The accustomed dose taken in a strange environment caused fatal complications because the conditioned tolerance failed to operate. The concentration of morphine in the blood did not exceed the level measured during earlier treatment. Conclusion These results are in line with the data in the literature indicating that morphine concentrations measured in cases of drug-related death do not differ substantially from those measured in cases where the outcome is not fatal. A knowledge of the conditioning mechanism can contribute to prevention of fatal cases of a similar type. The harm reduction approach places great stress on preventive intervention based on data related to drug-related death.